Applied behavior analysis in early childhood education an introduction to evidence-based interventions and teaching strategies - Casey, Laura Baylot 1976-; Carter, Stacy L. (Routledge, 2016)
Applied Behavior Analysis in Early Childhood Education provides a basic introduction to applied behavior analysis and the highly beneficial role that it can play in early childhood education for both typically developing children and those with special needs. The objective is to provide future and current early childhood professionals with the tools that they need to positively impact the lives of young children.